2023
DOI: 10.1101/2023.04.21.537763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleus accumbens neurons dynamically encode positive and aversive associative learning

Abstract: To survive, individuals must learn to associate cues in the environment with emotionally relevant outcomes. This association is partially mediated by the nucleus accumbens (NAc), a key brain region of the reward circuit that is mainly composed by GABAergic medium spiny neurons (MSNs), that express either dopamine receptor D1 or D2. Recent studies showed that both populations can drive reward and aversion, however, the activity of these neurons during appetitive and aversive Pavlovian conditioning remains to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
2
2
Order By: Relevance
“…In contrast, we showed that D1-and D2-MSNs within the NAc core exhibit a general decrease in activity in response to cues and outcomes throughout Pavlovian learning, with dynamic and partially overlapping activity responses to both stimuli [19]. In aversive Pavlovian conditioning, both D1-and D2-MSNs increase activity in response to the cue and to the negative outcome (mild foot shock) [19]. Other studies report that both NAc shell D1-and D2-MSNs increase activity when mice withhold operant responses to unproductive reward seeking, suggesting that efficient reward seeking relies on complementary activity across NAc cell types [96].…”
Section: Calcium Imaging Evidencecontrasting
confidence: 65%
See 3 more Smart Citations
“…In contrast, we showed that D1-and D2-MSNs within the NAc core exhibit a general decrease in activity in response to cues and outcomes throughout Pavlovian learning, with dynamic and partially overlapping activity responses to both stimuli [19]. In aversive Pavlovian conditioning, both D1-and D2-MSNs increase activity in response to the cue and to the negative outcome (mild foot shock) [19]. Other studies report that both NAc shell D1-and D2-MSNs increase activity when mice withhold operant responses to unproductive reward seeking, suggesting that efficient reward seeking relies on complementary activity across NAc cell types [96].…”
Section: Calcium Imaging Evidencecontrasting
confidence: 65%
“…A very recent study using fibre photometry recordings of calcium signals (bulk activity) in the NAc during a Pavlovian approach task showed that D1-MSNs present multiphasic calcium events during cue presentation and reward delivery (increased activity to both cue and reward), whereas D2-MSNs present a monophasic event only after reward delivery [20]. In contrast, we showed that D1-and D2-MSNs within the NAc core exhibit a general decrease in activity in response to cues and outcomes throughout Pavlovian learning, with dynamic and partially overlapping activity responses to both stimuli [19]. In aversive Pavlovian conditioning, both D1-and D2-MSNs increase activity in response to the cue and to the negative outcome (mild foot shock) [19].…”
Section: Calcium Imaging Evidencecontrasting
confidence: 55%
See 2 more Smart Citations